A Role for CD81 and Hepatitis C Virus in Hepatoma Mobility - Brimacombe, Claire L. (MDPI, 2014)
Tetraspanins are a family of small proteins that interact with themselves, host transmembrane and cytosolic proteins to form tetraspanin enriched microdomains (TEMs) that regulate important cellular functions. Several tetraspanin family members are linked to tumorigenesis. Hepatocellular carcinoma (HCC) is an increasing global health burden, in part due to the increasing prevalence of hepatitis C virus (HCV) associated HCC. The tetraspanin CD81 is an essential receptor for HCV, however, its role in hepatoma biology is uncertain. We demonstrate that antibody engagement of CD81 promotes hepatoma spread, which is limited by HCV infection, in an actin-dependent manner and identify an essential role for the C-terminal interaction with Ezrin-Radixin-Moesin (ERM) proteins in this process. We show enhanced hepatoma migration and invasion following expression of CD81 and a reduction in invasive potential upon CD81 silencing. In addition, we reveal poorly differentiated HCC express significantly higher levels of CD81 compared to adjacent non-tumor tissue. In summary, these data support a role for CD81 in regulating hepatoma mobility and propose CD81 as a tumour promoter.